Introduction - Dominguez, Virginia R. (Review of International American Studies, 2018)
Virginia R. Dominguez University of Illinois at Urbana-Champaign USA Walls, Material and Rhetorical: Past, Present, and Future Abstract: An introduction to this special issue of RIAS on walls, in light of President Trump’s proposal to build a tall and beautiful wall along the US-Mexico border and the multiple concerns it raises, this essay, like this issue of RIAS as a whole, provides comparative background on walls built at different times in the past and in different locations around the world, exploring their intended efficacy and questionable results, their transformation over time into sites of tourism, uncertain peace, and unstable truces. Raising questions about both rhetoric and materiality, it suggests that the matter does not just concern Trump’s views and policies but, rather, much more general views in the US toward Mexico and Mexicans. The essay raises the specters of both racism and imperialism in the rhetoric and proposals coming from the White House, and it seeks to use contributions from scholars in Italy, Israel, Mexico, the U.S., Hungary, South Korea, Denmark, and Canada to put it all in broader perspective. Keywords: Trump’s proposed wall, introduction, rhetoric, polls, comparisons